Impacto da aflatoxina B1, montmorilonita e β-glucana na fermentação ruminal in vitro - Dal Pozzo, Marcelo (2015)
The effects of aflatoxin B1 (AFB1) (1μg/mL) were evaluated and sorbents β-glucans derived from Saccharomyces cerevisae with 65% of active ingredient (β-glu) (1mg/mL) and montmirillonite (MMT) (5mg/mL) under ruminal fermentation. Two in vitro assays were conducted. On the first assay the objectives were to determine the production of short chain fatty acids, the production of ammonia during 24-h in vitro. While on the second assay the production of methane (CH4) and kinetic parameters based on gas production date were determined (GPmax= maxim gas production in t time; Lag= lag phase before gas production commenced; S=gas production rate (h-1)) during 72-h in vitro incubation. In each assay six repetitions were made for the following treatments: CONT: control (without AFB1 or sorbents); AF: AFB1 (1μg/mL); β-glu (1mg/mL); β-glu + AF: (1mg/mL of β-glu + 1μg/mL of AFB1); MMT: (5mg/mL); MMT + AF: (5mg/mL of MMT + 1μg/mL of AFB1). The amount of AGCC produced by the β-glu (67,7 mM) treatment was significantly higher about CONT (57,72 mM) and MMT (53,3 mM). treatments. On the other hand, MMT clay reduced the production of NH3 (9,6 mM) about CONT (11,4 mM), AF (12,6 mM) and β-glu (12,2 mM). The amount of GPmax by the β-glu treatment was 103,4 mL, significantly higher about produced CONT (89,0 mL) e MMT (91,6 mL). There was also higher gas production rate by the β-glu treatment. The montmorilonite raised the lag phase and reduced the CH4 production. The results of this study suggest that AFB1 (1μg/mL) has no toxic effect on ruminal fermentation. Whereas the β-glu impacts the ruminal fermentation by increase the AGCC produced. The montmorilonite can delay the bacterial colonization but does t effect the quantity of AGCC produced.